2021
DOI: 10.1108/imds-12-2019-0722
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement learning for content's customization: a first step of experimentation in Skyscanner

Abstract: PurposeThe aim of the paper is to test and demonstrate the potential benefits in applying reinforcement learning instead of traditional methods to optimize the content of a company's mobile application to best help travellers finding their ideal flights. To this end, two approaches were considered and compared via simulation: standard randomized experiments or A/B testing and multi-armed bandits.Design/methodology/approachThe simulation of the two approaches to optimize the content of its mobile application an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Researchers increasingly use Big Data from mobile applications, social networks and web tools to better monitor and understand the needs of tourists (Li & Law, 2020;Li, Xu, Tang, Wang, & Li, 2018). This study uses data from Skyscanner, a travel metasearch engine used monthly by >100 million people worldwide (Giachino, Bollani, Bonadonna, & Bertetti, 2021). Skyscanner allows users to define the search parameters (origin, destination, travel dates, number of travellers, etc.)…”
Section: Phase 1: Database Analysismentioning
confidence: 99%
“…Researchers increasingly use Big Data from mobile applications, social networks and web tools to better monitor and understand the needs of tourists (Li & Law, 2020;Li, Xu, Tang, Wang, & Li, 2018). This study uses data from Skyscanner, a travel metasearch engine used monthly by >100 million people worldwide (Giachino, Bollani, Bonadonna, & Bertetti, 2021). Skyscanner allows users to define the search parameters (origin, destination, travel dates, number of travellers, etc.)…”
Section: Phase 1: Database Analysismentioning
confidence: 99%
“…However, existing methods of customizing and distributing teaching content still face many challenges in practical application. First, many methods fail to fully consider the configuration of teaching content combinations and its complex relationship with students' needs, resulting in distributed content not optimally meeting their needs [23][24][25]. Second, existing teaching content distribution methods are often complex and require a large amount of computing resources, which is not feasible in large-scale educational scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The twelfth article, co-authored by Chiara Giachino, Luigi Bollani, Alessandro Bonadonna and Marco Bertetti, is "Reinforcement learning for content's customization: a first step of experimentation in Skyscanner," which tests the potential benefits of applying reinforcement learning to optimize the content of a company's mobile application to best help travelers find their ideal flights. The authors found that simulation of reinforcement learning provides potential benefits for travelers (Giachino et al, 2021).…”
mentioning
confidence: 99%